Combination Therapy With Tocilizumab and Dexamethasone Cost-Effectively Reduces Coronavirus Disease 2019 Mortality. (6th May 2021) - Sinha, Pranay; Linas, Benjamin P
Abstract: Recent randomized trials suggest that interleukin-6 inhibitors reduce mortality due to severe coronavirus disease 2019. Using a decision tree model, we found that tocilizumab is cost-effective with an estimated incremental cost-effectiveness ratio of 16 520 per quality-adjusted life year gained (95% credible interval, 10 760–51 530).